1996
DOI: 10.1056/nejm199611073351906
|View full text |Cite
|
Sign up to set email alerts
|

Injuries Due to Firearms in Three Cities

Abstract: Injuries due to firearms, most involving handguns, are a major cause of morbidity and mortality in U.S. urban areas. The incidence varies greatly from city to city.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
42
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(52 citation statements)
references
References 32 publications
8
42
2
Order By: Relevance
“…Although several studies have stated this rate as ranging between 62.2%-71.80%, it was determined by Solarino et al [4] as 88.4%, by Kellermann [28] as 88%, by Guileyardo [29] as 65%, by Riddick [30] as 53%, by Al Ragheb [31] as 51%, by Verzeletti et al [32] as 35.9%, and by Druid [27] as 18.7%. While the results of the current study are similar to those of some previous studies, they are also different from those of some others.…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have stated this rate as ranging between 62.2%-71.80%, it was determined by Solarino et al [4] as 88.4%, by Kellermann [28] as 88%, by Guileyardo [29] as 65%, by Riddick [30] as 53%, by Al Ragheb [31] as 51%, by Verzeletti et al [32] as 35.9%, and by Druid [27] as 18.7%. While the results of the current study are similar to those of some previous studies, they are also different from those of some others.…”
Section: Discussionmentioning
confidence: 99%
“…A study of patients who survived a suicide attempt found that 47.6% of patients reported that the time between thinking about committing suicide and the actual attempt was 10 minutes or less. 3 Suicide attempts using a firearm result in death 86% of the time 4 ; ingestion of drugs or poisons with the intent to commit suicide is successful less than 2% of the time.…”
Section: In This Issuementioning
confidence: 99%
“…A three-city study found that 9 % of medically documented cases of gunshot injuries could not be matched with a corresponding police report. 16,17 Other US studies on the recording of WHO SHOT YA? HOW EMERGENCY DEPARTMENTS CAN COLLECT RELIABLE POLICE... S13…”
Section: Death In Custody Reporting Actmentioning
confidence: 99%